Analysis of Service Quality of Front Office Staff in Increasing Guest Satisfaction - Ni Luh Gede Agustina Dewi; I Gusti Putu Sutarma; I Ketut Sutama; Ni Made Ernawati (International Journal of Glocal Tourism, 2022)
Purpose: The purpose of this research was to know how the service quality of the Front Office Staff at a 3 star hotel in Legian, Kuta, Bali and which indicators need to be improved and maintained in the service quality carried out . Research methods: The data collection methods used in this research were observation, questionnaires, and literature study. The sample used in this research amounted to 85 respondents. Data obtained through distributing questionnaires that have been tested using validity and reliability tests. The analysis techniques used in this research are Service Quality (Servqual) and Importance Performance Analysis (IPA). Findings: The results of the IPA show that the positive service quality score gap is more than the negative service quality score gap, that the service quality of the Front Office Staff as a whole has shown a good service quality and be able to satisfy of guests. Implication: There are there are three indicators that must be improved in the service quality of the Front Office Staff, are: indicators (X6), indicators (X7), and indicators (X10). Seven indicators need to be maintained in the service quality of Front Office Staff, are: indicators (X2), indicators (X3), indicators (X4), indicators (X5), indicators (X11), indicators (X14), and indicators (X17).